PODCAST AUDIO-ASSISTED LISTENING IN A SENIOR HIGH SCHOOL ENGLISH CLASS : A Case Study in a Private Senior High School English Class - Hemalia Damayanti, - (2019)
This research paper explores students' responses toward podcast audio-assisted listening skill in a senior high school which consisted 18 students. Qualitative method with case study design is used for this research. Podcast audio heard by students are accommodated in the curriculum used in the school. As a result, podcast audio helps students in learning listening skill based on three categories: students' cognitive, affective, and psychomotor. Most of the students know that it is an application that is available in their smartphone that they use in the daily life, so they can access it anytime and anywhere. Podcast involves interesting contents that make the students interested in hearing them, i.e. Chance to live, Natural World, and News Report. The finding in this research includes increasing students' concentration in learning the materials, and better motivation of the students to study listening subject.